Cervical Spondylotic Myelopathy: Factors in Choosing the Surgical Approach - Praveen K. Yalamanchili; Michael J. Vives; Saad B. Chaudhary (Advances in Orthopedics)
Cervical spondylotic myelopathy is a progressive disease and a common cause of acquired disability in the elderly. A variety of surgical interventions are available to halt or improve progression of the disease. Surgical options include anterior or posterior approaches with and without fusion. These include anterior cervical discectomy and fusion, anterior cervical corpectomy and fusion, cervical disc replacement, laminoplasty, laminectomy with and without fusion, and combined approaches. Recent investigation into the ideal approach has not found a clearly superior choice, but individual patient characteristics can guide treatment.